Dilated cardiomyopathy caused by a pathogenic nucleotide variant in RBM20 in an Iranian family - Mahshid Malakootian; Mahrokh Bagheri Moghaddam; Samira Kalayinia; Melody Farrashi; Majid Maleki; Parham Sadeghipour; Ahmad Amin (BMC, 2022)
Abstract Introduction Dilated cardiomyopathy (DCM) is characterized by the dilation and impaired contraction of 1 or both ventricles and can be caused by a variety of disorders. Up to 50% of idiopathic DCM cases have heritable familial diseases, and the clinical screening of family members is recommended. Identifying a genetic cause that can explain the DCM risk in the family can help with better screening planning and clinical decision-making. Whole-exome sequencing (WES) has aided significantly in the detection of causative genes in many genetically heterogeneous diseases. In the present study, we applied WES to identify the causative genetic variant in a family with heritable DCM. Methods WES was applied to identify genetic variants on a 26-year-old man as the proband of a family with DCM. Subsequently, Sanger sequencing was performed to confirm the variant in the patient and all the available affected and unaffected family members. The pathogenicity of the variant was evaluated through co-segregation analysis in the family and employment of in silico predictive software. Results WES demonstrated the missense pathogenic heterozygous nucleotide variant, c.1907G > A, (p.Arg636His, rs267607004, NM_0011343), in exon 9 of the RBM20 gene in the proband. The variant was co-segregated in all the affected family members in a heterozygous form and the unaffected family members. The in silico analysis confirmed the variant as pathogenic. Conclusion Pathogenic RBM20 nucleotide variants are associated with arrhythmogenic DCM. We believe that our report is the first to show an RBM20 variant in Iranian descent associated with DCM.